Representasi Emosi Remaja dan Pengaruhnya terhadap Hubungan Sosial dalam Film Animasi “Inside Out 2”: Penelitian - Marssel Michael Sengkey; Nova Lisye Sinaulan; Gloria Natalie Lantu; Hestria Br Ginting; Giva Syaloom Sembor (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Adolescence is a crucial period marked by strong emotions and the search for identity, which greatly affect social relationships. Inside Out 2 introduces new emotions such as anxiety, envy, shame, and boredom, reflecting the complexity of emotions experienced by adolescents. The purpose of this study is to explore how adolescent emotions are depicted in Inside Out 2 and how they affect the social relationships of the main character, Riley. This study uses a descriptive qualitative method with Roland Barthes' visual semiotic analysis and a developmental psychology approach. The findings of the analysis indicate that the visual design and behavior of the emotional characters symbolically depict the psychological dynamics of adolescents, as well as how unmanaged emotions can disrupt social relationships and influence negative self-perceptions. This film not only functions as a means of entertainment, but also as an effective educational medium in increasing understanding of the importance of emotional intelligence and emotional management in adolescents. These results support the potential of animated films as psychological learning tools that can be used in various disciplines.